Strategies for Enhancing Urban Drainage System Performance in Reducing Inundation Risk: A Literature Review with Implications for Bone Regency - Edhi Kurniawan; M Awaluddin A; ST Nurfaiza (Jurnal Teknik Sipil, 2026)
Rapid urban development increases surface runoff and reduces soil infiltration capacity, thereby amplifying the risk of inundation due to the imbalance between runoff discharge and drainage system capacity. This issue is not confined to major metropolitan areas but has also begun to emerge in developing regions such as Bone Regency. This study aims to identify strategies for enhancing the performance of urban drainage systems based on systems and resilience-oriented approaches, and to formulate their implications for reducing inundation risk in Bone Regency. The research adopts a qualitative approach using a narrative literature review method, encompassing national and international publications from 2000 to 2025. The analysis was conducted through thematic synthesis of key concepts, including system performance indicators, the integration of gray and green infrastructure, and urban drainage resilience frameworks. The findings indicate that improving drainage performance must be grounded in comprehensive evaluation of hydrological and hydraulic indicators, runoff control at the source through nature-based solutions, and the application of system flexibility and adaptive capacity principles. Such an integrated approach is highly relevant for supporting more responsive and sustainable drainage planning in Bone Regency. This study provides a conceptual contribution by developing a systemic and long-term performance enhancement framework for urban drainage systems.